2017
DOI: 10.4236/jbm.2017.52004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antifungal Activity of Naphthoquinones Dimeric Derived from Lawsone

Abstract: This article reports the evaluation of antioxidant and antifungal activity from synthetic naphthoquinones derived from lawsone. The antifungal activity was carried out through the inhibition of exoenzymes produced by Candida albicans. The inhibition of phospholipase and the proteinase production by Candida was similar in all derivatives tested; however, the difference between the enzyme production of the control and test does not show statistical difference in any of the studied strains. Furthermore, the antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…It should be noted that higher ABTS values may be attributed to the ABTS• + (radical) stability over a wide pH range, the high sensitivity test, and the fast radical–antioxidant reaction. Moreover, ABTS• + is reactive toward most antioxidants, supporting the evaluation of a wide range of antioxidants, including hydrophilic and lipophilic compounds [ 75 , 76 ] The observed antioxidant capacity levels of the R. nasutus leaf extract were in good agreement with the results from other investigators [ 69 , 72 , 77 ]. In summary, the SCC extract exhibited a high antioxidant potential equivalent to that of the leaf extract, suggesting the possibility of using the SCC extract in further applications.…”
Section: Discussionsupporting
confidence: 77%
“…It should be noted that higher ABTS values may be attributed to the ABTS• + (radical) stability over a wide pH range, the high sensitivity test, and the fast radical–antioxidant reaction. Moreover, ABTS• + is reactive toward most antioxidants, supporting the evaluation of a wide range of antioxidants, including hydrophilic and lipophilic compounds [ 75 , 76 ] The observed antioxidant capacity levels of the R. nasutus leaf extract were in good agreement with the results from other investigators [ 69 , 72 , 77 ]. In summary, the SCC extract exhibited a high antioxidant potential equivalent to that of the leaf extract, suggesting the possibility of using the SCC extract in further applications.…”
Section: Discussionsupporting
confidence: 77%
“…In order to achieve this, another natural molecule lawsone (2-hydroxy-1, 4-naphthoquinone) (a chemical constituent of the henna plant) was also selected based on its demonstratable anticancer activity [ 35 , 36 ]. The 1,4-naphthoquinone pharmacophore has been at the center of numerous studies and has reported biological activity via a dianion species or radical anion [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve this, another natural molecule lawsone (2-hydroxy-1, 4-naphthoquinone) (a chemical constituent of the henna plant) was also selected based on its demonstratable anticancer activity [ 35 , 36 ]. The 1,4-naphthoquinone pharmacophore has been at the center of numerous studies and has reported biological activity via a dianion species or radical anion [ 36 ]. Quinone moieties are present in several anticancer drugs including daunorubicin, doxorubicin and mitoxantrone [ 37 ] and many derivatives synthesized from 2-hydroxy-1,4-naphthoquinone have been demonstrated to have anticancer activity [ 38 ] resulting from redox cycling, arylation, intercalation, the induction of DNA strand breaks, the generation of free radicals and alkylation via quinone methide formation [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Particularly, trifluoromethyl-substituted compound induced apoptosis in the glioma cells by inducing the caspase dependent apoptotic pathways via ROS and downregulating the PI3 K/AKT/mTOR pathway. Several bis-lawsone derivatives were found to exhibit antioxidant, antifungal, 5 antibacterial, 6 and antileishmanial activities 7 as well as inhibit against HIV-1 integrase, 8 and H5N1 neuraminidase. 9 Due to the broad biological relevance of 3,3´-(arylmethylene)bis(2-hydroxynaphthalene-1,4-diones), considerable efforts have been paid on the improvement of synthetic approaches of this class of compounds for the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…4 Particularly, trifluoromethyl-substituted compound induced apoptosis in the glioma cells by inducing the caspase dependent apoptotic pathways via ROS and downregulating the PI3 K/AKT/mTOR pathway. Several bis -lawsone derivatives were found to exhibit antioxidant, antifungal, 5 antibacterial, 6 and antileishmanial activities 7 as well as inhibit against HIV-1 integrase, 8 and H5N1 neuraminidase. 9…”
Section: Introductionmentioning
confidence: 99%